Angiogenin and vascular endothelial growth factor expression in lungs of lung cancer patients - Rozman, Aleš (Radiology and oncology (Ljubljana), 2012)
Background. Lung cancer is the leading cause of cancer deaths. Angiogenesis iscrucial process in cancer growth and progression. This prospective study evaluated expression of two central regulatory molecules: angiogenin and vascular endothelial growth factor (VEGF) in patients with lung cancer. Patients and methods. Clinical data, blood samples and broncho-alveolar lavage(BAL) from 23 patients with primary lung carcinoma were collected. BAL fluid was taken from part of the lung with malignancy, and from corresponding healthy side of the lung. VEGF and angiogenin concentrations were analysed by an enzyme-linked immunosorbent assay. Dilution of bronchial secretions in the BAL fluid was calculated from urea concentration ratio between serum and BAL fluid. Results. We found no statistical correlation between angiogenin concentrations in serum and in bronchial secretions from both parts of the lung. VEGF concentrations were greater in bronchial secretions in the affectedside of the lung than on healthy side. Both concentrations were greater than serum VEGF concentration. VEGF concentration in serum was in positive correlation with tumour size (p = 0,003) and with metastatic stage ofdisease (p = 0,041). There was correlation between VEGF and angiogenin concentrations in bronchial secretions from healthy side of the lung and between VEGF and angiogenin concentrations in bronchial secretions from part of the lung with malignancy. Conclusion. Angiogenin and VEGF concentrations insystemic, background and local samples of patients with lung cancer are affected by different mechanisms. Pro-angiogenic activity of lung cancer has an important influence on the levels of angiogenin and VEGF.
Keywords: Angiogenesis Factor; Angiogenetski faktor; Bronchoalveolar Lavage Fluid; Bronhoalveolarni izpirek, tekočina; Endotelij žilni; Endotelijski, rastni faktorji; Endothelial Growth Factors; Endothelium, Vascular; Lung Neoplasms; Pljučne novotvorbe; Prospective Studies; Prospektivne študije